Advance Care Plan and Factors Related to Disease Progression in Patients With Spinocerebellar Ataxia Type 1: A Cross-Sectional Study in Thailand - Patama Gomutbutra (2019)
© The Author(s) 2019. Background: Spinocerebellar ataxia type 1 (SCA1) is an autosomal dominant progressive neurodegenerative disease. Few studies have been conducted regarding advance care planning in this population. Objective: This study explores advance care planning preferences of patients with SCA1 and their association with disease progression and quality of life. Methods: The study examined 12 Thai patients with SCA1 from 2 families living in Thailand. The advance care plan followed a Gold Standards Framework. The 12 patients were interviewed and recorded in video. The research team evaluated neurocognitive functions as measured by the following tests; Scale for the Assessment and Rating of Ataxia (SARA), Berg Balance Score, Mini-Mental Status Examination, and Digit Span and Category Fluency. The quality of life was measured by a Short-Form Health Survey-36 (SF-36). Results: Seven of 12 patients with SCA1 rated communication ability as most important for their quality of life. Patients identified becoming a burden on their family members and ventilator dependence as the most undesirable situations. Half of the patients preferred a hospital as their last place of care. Comparing patients prefer hospital to home has significantly high median SARA (23 vs 11.5; P =.03) and low SF-36 (41.4 vs 72.4; P =.02). Conclusions: Those patients preferring a hospital for end-of-life care exhibited more physical disability and lower quality of life than those who preferred home care. Making assisted living health-care services in the home more readily available and affordable may alleviate concerns of patients facing more severe physical challenges.